1997
DOI: 10.1083/jcb.138.3.495
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase D Stimulates Release of Nascent Secretory Vesicles from the trans-Golgi Network

Abstract: Phospholipase D (PLD) is a phospholipid hydrolyzing enzyme whose activation has been implicated in mediating signal transduction pathways, cell growth, and membrane trafficking in mammalian cells. Several laboratories have demonstrated that small GTP-binding proteins including ADP-ribosylation factor (ARF) can stimulate PLD activity in vitro and an ARF-activated PLD activity has been found in Golgi membranes. Since ARF-1 has also been shown to enhance release of nascent secretory vesicles from the TGN of endoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
213
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 253 publications
(232 citation statements)
references
References 64 publications
16
213
3
Order By: Relevance
“…The sequence and distribution of two PLD isoforms, PLD1 and PLD2, have been reported (Colley et al, 1997;Exton, 1998) PLD1 has a low basal activity and can be regulated by PKC, PtdIns(4,5)P 2 and small GTPbinding proteins (Exton, 1998) and PLD2 has a high basal activity and can be activated by fatty acids (Kim et al, 1999). The lipid product of PLD activity, PA, itself can induce a number of cellular functions and it can be converted by PA phosphohydrolase (PAP) into DAG, which is an activator of PKC (Chen et al, 1997;Hodgkin et al, 1998;Nishizuka, 1995). While it is possible that PLD activation requires a coordinated cross-talk between those signalling molecules, there is strong evidence that the activation of small G-proteins and PKC can occur independently of each other.…”
Section: Introductionmentioning
confidence: 99%
“…The sequence and distribution of two PLD isoforms, PLD1 and PLD2, have been reported (Colley et al, 1997;Exton, 1998) PLD1 has a low basal activity and can be regulated by PKC, PtdIns(4,5)P 2 and small GTPbinding proteins (Exton, 1998) and PLD2 has a high basal activity and can be activated by fatty acids (Kim et al, 1999). The lipid product of PLD activity, PA, itself can induce a number of cellular functions and it can be converted by PA phosphohydrolase (PAP) into DAG, which is an activator of PKC (Chen et al, 1997;Hodgkin et al, 1998;Nishizuka, 1995). While it is possible that PLD activation requires a coordinated cross-talk between those signalling molecules, there is strong evidence that the activation of small G-proteins and PKC can occur independently of each other.…”
Section: Introductionmentioning
confidence: 99%
“…Golgi membranes isolated from cells overexpressing PLD 1 show elevated production of PtdIns(4,5)P 2 (294), consistent with stimulation of a PIP5KI enzyme by PA. In a series of studies, Shields and colleagues (322,323,346) have shown that PtdIns(4,5)P 2 is required to maintain Golgi structure and its production is regulated through the production of PA. Overexpression of a dominant negative PI4KII␤ disrupts the structure of the Golgi, perhaps by interfering with the ability of spectrin to bind to membranes (120), although it is not clear if this is due to the lack of a precursor for PtdIns(4,5)P 2 or to a direct effect of insufficient PtdIns(4)P. The release of secretory vesicles exporting hormones from the TGN requires PtdIns(4,5)P 2 (42,324). The nature of the vesicle coat, if any, involved in this transport step is not known.…”
Section: E Ptdins(4)p and Ptdins(45)p 2 On The Golgimentioning
confidence: 99%
“…However, PLD1 overexpression failed to increase the number of ␤APP-containing vesicles budded from the TGN in PS1 Ϫ/Ϫ fibroblasts, probably because of a maximal rate of ␤APP-containing vesicle trafficking in PS1-null cells. Inhibition of PLD1 catalytic activity by 1-butanol (an inhibitor of PLD-catalyzed formation of PA) (11,16), resulted in decreased ␤APP trafficking from the TGN in both PS1wt and PS1 Ϫ/Ϫ cells (Fig. 1b).…”
Section: Pld1mentioning
confidence: 99%
“…PLD has been shown to regulate membrane trafficking events, such as the release of secretory vesicles from the TGN (11), endocytosis (12) and exocytosis (13), and actin dynamics (14). In this study, the effects of PLD1 on ␤APP trafficking have been investigated.…”
mentioning
confidence: 99%